The nexus between audit features and timely financial reporting in the GCC region: A moderating role for institutional ownership - Khan, Faisal; Abubakr, Ayman Abdalla Mohammed; Hussain, Shatha (International Journal of Innovative Research and Scientific Studies, 2025)
This research examines the nexus between audit features and timely financial reporting in the GCC region. The delay in submitting audit reports (ARL) amplifies uncertainty and diminishes confidence in financial statements. Thus, the study focuses on audit firm size, auditor change, busy audit season, institutional ownership (IO), and the timeliness of audit reports for non-financial companies listed on the stock exchanges of Gulf Cooperation Council (GCC) economies. The research draws on 5,271 firm-year observations spanning from 2009 to 2023. To test the hypotheses, the study employs both the generalized method of movements (GMM) technique combined with propensity score matching (PSM) approach. The study reveals that changes in auditors, a busy audit season, and the implementation of the Big 4 significantly increase the ARL in the GCC. Furthermore, institutional ownership cannot mitigate the detrimental effects of these three audit features on ARL. However, IO with at least a 20% stake significantly curtails the negative role of audit features in increasing the ARL in the region. Our research concludes that audit-related features and institutional ownership are very critical in preventing unnecessary delays in the audit report. The increasing ARL in GCC requires the regulator to revisit the legislation regarding the appointment of auditors, auditor change, busy audit season, and the stake of institutional ownership for the listed companies.